2018
DOI: 10.1111/iej.12982
|View full text |Cite
|
Sign up to set email alerts
|

Fracture incidence of instruments from a single‐file reciprocating system by students in an endodontic graduate programme: a cross‐sectional retrospective study

Abstract: The use of WaveOne and Reciproc single-file reciprocating systems in an endodontic graduate programme was associated with a low incidence of instrument fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 32 publications
1
33
1
3
Order By: Relevance
“…Regarding overall fatigue resistance, two systematic reviews found that instruments used in reciprocation have better CF resistance than rotary instruments (). A clinical study from an endodontic graduate programme found less than 1% instrument fracture using WaveOne reciprocating instruments (). When new instruments like EdgeFile X1 are introduced, it is important to study multiple properties including cutting efficiency, torsional resistance, CF resistance and flexibility, especially when they are manufactured with new alloys and there is a lack of information about their performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding overall fatigue resistance, two systematic reviews found that instruments used in reciprocation have better CF resistance than rotary instruments (). A clinical study from an endodontic graduate programme found less than 1% instrument fracture using WaveOne reciprocating instruments (). When new instruments like EdgeFile X1 are introduced, it is important to study multiple properties including cutting efficiency, torsional resistance, CF resistance and flexibility, especially when they are manufactured with new alloys and there is a lack of information about their performance.…”
Section: Introductionmentioning
confidence: 99%
“…The total incidence of file fractures in the present study was 3.9 patients/100 root canal-treated patients, which was higher when compared to that of earlier literature. [ 9 10 11 12 ] Multiple factors need to be addressed before comparing the present study results with those of the past literature. Variations in the study methodology, operator expertise, and instrumentation file systems of earlier studies, limit the comparison of the present study results with those of the past literature.…”
Section: Discussionmentioning
confidence: 98%
“…Although other authors have used stereomicroscopy [11,12], the use of scanning electron microscopy is justified because some fracture-related changes are seen at high magnifications only, which is not possible with an operation microscope [14]. The 4-mm region from the tip of the instrument was chosen for evaluation because it is where the fracture usually occurs [11,12,24], and mandibular molars were used because the incidence of instrument fracture is high in these teeth [11,17,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this topic should be considered in function of the number of reuses of the instruments in the clinical practice. Caballero-Flores and coauthors [25] observed that the WaveOne files can be clinically reused up to six root canals, with low incidence of fracture (0.92%). This finding is in accordance with our results because the disruption of cutting edges was the only statistically significant defect, increasing from the sixth use onwards.…”
Section: Discussionmentioning
confidence: 99%